(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2021)
In order for some persons to make friends, they indulge in social networking. Since the advent of matchmaking on social networks, many protocols have been proposed. However, security and privacy of users’ attributes are the main concerns in most of the existing matchmaking protocols. Also, much consideration has not been given to how many attributes users should have in common before they are matched. Furthermore, only the initiator knows the common attributes they have in common. These issues inhibit the full patronage of mobile social network by some persons as it encourages malicious operations. In lieu of these, this paper proposes protocol that is robust against the upmentioned security issues. In this protocol, the initiator sets a criterion for a match-pair to be made. Only users that meet this criterion qualify to be match-paired. Furthermore, in order to ensure privacy of users’ attributes, the attributes are exchanged only when they are match-paired and disclosed to the matched-pair only. The protocol can resist semihonest and malicious attacks.